Investigation of the VVER-1000 reactor pressure vessel neutron fluence and displacement per atom using MCNP6. (December 2020) - Tiep, Nguyen Huu; Hoang, Sy Minh Tuan; Hartanto, Donny; Kim, Kyung Doo; Kim, Jong Kyung; Tuan, Nguyen Minh; Ha, Pham Nhu Viet
Abstract: Ensuring the integrity of the reactor pressure vessel (RPV) during the operating life of nuclear reactors is of paramount importance, and hence the harmful effects of irradiation on the steels of the RPVs have been extensively studied especially the irradiation embrittlement effects. However, improvements in the calculation methods are still necessary to further reduce the discrepancy between calculations and experiments. This study was performed to examine the neutron fluence and respective rate of displacement per atom (DPA), an important parameter describing the irradiation-induced damage, in the VVER-1000 RPV steel based on the criticality calculation, instead of the common fixed source approach, with the MCNP6 Monte Carlo code, and identify the most sensitive locations in the VVER-1000 RPV. The MCNP6 modeling of the VVER-1000 reactor was verified against the OpenMC calculations in addition to the confirmation of the convergence of the effective neutron multiplication factor and the Shannon entropy of the fission source distribution in the MCNP6 criticality calculations to ensure reliable tally results of the neutron fluence. Consequently, the maximum neutron fluence in the VVER-1000 RPV was found at the positions adjacent to the peripheral fuel assemblies, and the respective DPA rate was analyzed in correlation with the neutron fluence and energy spectrum. Highlights: Neutron fluence and DPA rate at the VVER-1000 reactor pressure vessel were examined with MCNP6. Maximum locations of neutron fluences and DPA rates at the reactor pressure vessel were identified. The DPA rate at the reactor pressure vessel was largely attributed to the fast neutrons. Contribution of epithermal neutrons to the DPA rate can be as high as 8.13%. The DPA rate contribution by neutron energies from 4E-7 MeV–1 MeV increased through the reactor pressure vessel.